Navigating the Realm of Faculty Evaluation - Sonal Dekhane; Patrice Bell; Neelam Khan (Academic Chairpersons Conference Proceedings, 2022)
In this presentation the presenters will discuss annual evaluation process followed at a young, liberal arts institution. Chairs from three different STEM disciplines will provide an overview of the annual evaluation process and share strategies to ensure successful and consistent evaluation in departments of various sizes.
Keywords: faculty performance review; annual evaluation; faculty; leadership; management